INDIVIDUAL APPROACH TO ECONOMIC LITERACY IN THE UZBEK LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this article, we analyzed the role of the Uzbek language and its specific approaches in the process of improving economic literacy in Uzbekistan. Language is an important tool for understanding and transmitting economic knowledge to the general public, and the scientific, popular and understandable nature of this tool is one of the factors determining the effectiveness of economic reforms. The article examines the interpretation of economic terms in the Uzbek language, their use in the education system and the media, as well as their impact on the formation of economic ideas among the population.